Clinical management and supervision of Influenza – systematic review - Głodzik, Michał; Miśkiewicz, Marek; Łęcka, Martyna; Ogiegło-Kowalczyk, Aleksandra; Samborska, Julia; Stelmaszak, Karina; Stencel, Katarzyna; Więckowiak, Paweł; Wojtasik, Monika; Żak, Katarzyna (Journal of Education, Health and Sport, 2024)
The main aim of the following study is to review current knowledge on Influenza. Influenza, also known as the flu, is an acute, infectious disease which attacks the respiratory system. The disease is caused by the influenza virus, of which there are 3 types. The most common is type A of influenza virus. It is transmitted between people by the droplet route, with cases occurring particularly frequently during seasonal epidemics. This is why the most important form of prevention is maintaining personal hygiene and isolation of sick people. Another form of prevention is a vaccine for the influenza virus developed with new variants every year. The flu causes a variety of symptoms from many systems but can also be asymptomatic. Diagnosis of the illness is based on clinical criteria and the results of diagnostic tests for which there are established criteria of legitimacy. Most common and sufficient curation for an illness is a symptomatic treatment but there is also a causal treatment for influenza. However certain conditions are required for its implementation. Influenza is usually a mild disease, but there are present cases of serious complications. Groups particularly exposed to severe and complicated courses of the disease are pregnant women, children and patients with multimorbidities. Currently, the co-occurrence of influenza with Covid-19 infection is particularly dangerous, which constitutes a new challenge for the global health care system.